Activation‐dependent cell death of human monocytes is a novel mechanism of fine‐tuning inflammation and autoimmunity. Issue 8 (27th May 2016) - Däbritz, Jan; Weinhage, Toni; Varga, Georg; Wirth, Timo; Ehrchen, Jan M.; Barczyk‐Kahlert, Katarzyna; Roth, Johannes; Schwarz, Tobias; Foell, Dirk
Abstract : Simultaneous stimulation of monocytes with T‐cell derived GM‐CSF and IFN‐γ drives chronic inflammation and autoimmunity. Here, we show that hyperactivated monocytes undergo a caspase‐independent but cathepsin B‐ and TNF‐α mediated cell death with morphological characteristics of necrosis. This mechanism might prevent chronic inflammation and autoimmune reactions . Abstract : In patients with juvenile idiopathic arthritis (JIA), increased release of IFN‐γ and GM‐CSF in cells infiltrating synovial tissue can be a potent driver of monocyte activation. Given the fundamental role of monocyte activation in remodeling the early phases of inflammatory responses, here we analyze the GM‐CSF/IFN‐γ induced activity of human monocytes in such a situation in vitro and in vivo. Monocytes from healthy donors were isolated and stimulated with GM‐CSF ± IFN‐γ. Monocyte activation and death were analyzed by flow cytometry, immunofluorescence microscopy, ELISA, and qPCR. T‐cell GM‐CSF/IFN‐γ expression and monocyte function were determined in synovial fluid and peripheral blood from 15 patients with active JIA and 21 healthy controls. Simultaneous treatment with GM‐CSF and IFN‐γ induces cell death of monocytes. This cell death is partly cathepsin B‐associated and has morphological characteristics of necrosis. Monocytes responding to costimulation with strong proinflammatory activities are consequently eliminated. Monocytes surviving this form of hyperactivation retain normal cytokine production. Cathepsin B activity is increased in monocytes isolated from synovial fluid from patients with active arthritis. Our data suggest GM‐CSF/IFN‐γ induced cell death of monocytes as a novel mechanism to eliminate overactivated monocytes, thereby potentially balancing inflammation and autoimmunity in JIA.